ANALYSIS OF COOPERATIVE PRINCIPLES IN THE MAIN CHARACTER OF THE FILM BRIDGE TO TERABITHIA - Nenni Triana Sinaga; Renatha Samanta Br Samosir; Kammer Tuahman Sipayung (Program Studi Pendidikan Bahasa Inggris, 2024)
The cooperative principle is a term used in conversation to provide information to the speaker and listener. This research aims to analyze the types of cooperative principles and find out the most dominant types of maxims of cooperative principles on the main character in the film